Time-dependent effect of desensitization with wasp venom on selected parameters of the immune system - Łukasz Szymański; Weronika Urbańska; Martyna Ciepielak; Aleksandra Cios; Wanda Stankiewicz; Marta Stelmasiak; Agnieszka Rzeszotarska; Jolanta Korsak; Sławomir Lewicki; Andrzej Chciałowski (Scientific Reports, 2022)
Abstract The emergence of tolerance during Hymenoptera venom immunotherapy (VIT) is a complex process. The main goal of VIT is to induce a change from proinflammatory Th2 response to the Th1 response. However, the immune mechanism of acquiring rapid tolerance during VIT has not yet been fully understood. Therefore, we have analyzed (in 4-time points: 0, 2, 6, and 24 weeks after the initiation phase of VIT) the concentration of complement C3, C4, and C5 components, lymphocyte subpopulations (flow cytometry), as well as histamine and tryptase serum concentrations of 43 patients with wasp venom allergy (III and IV Müller grade) classified to ultra-rush treatment and 18 volunteers as the control group (CG). We observed that VIT affected the immune system by inducing changes in the complement system (decreased C3 and C4 compartment protein concentrations) and "normalized" the percentage of lymphocytes and neutrophils in the peripheral blood. Moreover, a significant increase in the percentage of nTreg in the blood of patients treated with VIT was observed. On the other hand, there were no changes in histamine or tryptase concentrations in the blood. Increased percentage of nTreg cells is a well-known mechanism by which VIT affects the immune system. Finally, VIT also modulated the concentrations of the complement components, which may be a previously unknown VIT mechanism of action.